Sistem Informasi Permohonan Bibit Di Balai Pengelolaan Daerah Aliran Sungai Pemali Jratun (BPDAS Pemali Jratun) Menggunakan Framework Flask - Maulana, Maulana; Heribertus Yulianton (Jurnal Mahajana Informasi, 2023)
The ability of a database to store significant amounts of data must be balanced with the speed with which users can access the information they need so that technological developments can keep up with the changing needs of users. In today's fast-paced and sophisticated world, an information technology service must be able to respond to data requests and process data quickly and effectively. However, when processing data, a system that stores too much data will inevitably encounter time constraints. By creating a web-based seed application information system, it can assist agencies in inputting community data, it can also assist organizations in online seed marketing using the Flask Framework. The results of the study show that this system makes it easy to view and record data, making it easier for officers at BPDAS Pemali Jratun to improve service to the community.